Είμαστε μόνοι στο συμπάν; Οι μετεωρίτες δίνουν απαντήσεις; - Μπαζιώτης Ι.; Taylor, L. A. (Bulletin of the Geological Society of Greece, 2013)
The humankind, despite the recent technological achievements, does not yet have the ability to carry out routine trips to nearby celestial bodies. However, space science is a reality. The “Apollo” missions, that took place during the period 1969-1972, included the moon landing, the walk of astronauts and collection of valuable samples. Since then, no similar space journey has been carried out. The possibility for future missions such as the return to the Moon or Mars, or to an asteroid (e.g., Vesta), seems small enough to be implemented in the next decades. Nevertheless, nature has the mechanism and procedures to resolve this problem by sending extra-terrestrial rocks in earth in the form of meteorites. Meteorite fall on Earth is a major event, as it reveals important information about the primordial stages of formation of our solar system, or the creation processes of other planets. However, the big question still remains; whether these rocks host or have traces of past life in turn employs researchers in the last twenty years. McKay et al. (1996) studied the meteorite ALH 84001 originating from Mars, claimed for important discoveries such as structures corresponding to nanobacteria. In the current paper, we focus on the origin of Martian meteorites, presenting their complete geological history; from the genesis of their protoliths till their falling to the earth. We attempt to shade light in the understanding of meteorite formation using mineralogical-petrological-geochemical data, and the assignment of timing for each event based upon contemporary geochronological data. Recently, studies of the Martian meteorite Tissint, allegedly discovered structures rich in carbon and oxygen. Furthermore, recent field observations from Curiosity rover, indicates the existence of surface water that flowed once in the past at the Martian surface. We conclude that the planet Mars might not be a "dead" planet. But it turns out that many of the meteorites that reach the Earth, have undergone a complex history which is associated with the development of very high pressures and temperatures on the surface of the planet (e.g., Mars) from which they originate, able to destroy any trace of life before them. After all, we should be very sceptic and evaluate all the possibilities before the acceptance for the existence of life out there.